Policies and governance for skills development in the fourth industrial revolution - Mohd Aizuddin Saari; Nur Atiqah Jalaludin; Mohamad Sattar Rasul; Mohamad Hidir Mhd Salim; Zool Hilmi Mohamed Ashari (International Journal of Evaluation and Research in Education (IJERE), 2026)
The fourth industrial revolution (4IR) has intensified policy concerns regarding the capacity of technical and vocational education and training (TVET) systems to support future workforce development. While national strategies increasingly emphasize skills development for industry 4.0, less attention has been paid to the governance mechanisms that shape policy coherence and implementation. This study examines skills governance within Malaysia’s TVET system, focusing on how policy alignment, quality assurance (QA), institutional coordination, and industry engagement influence workforce readiness for the 4IR. Adopting a qualitative approach, data were collected through focus group discussions (FGD) with key stakeholders from government agencies, industry, and TVET institutions, and analyzed thematically. The findings identify four key governance dimensions which are security procedures and policies in managing skills data, QA and standards, collaboration policy between institution and industry, and strengthens curriculum developments. Despite strong policy commitments, fragmented governance arrangements continue to constrain the effectiveness of skills development initiatives. By reframing skills development as a governance challenge, this study contributes to policy futures debates and offers insights for strengthening integrated and future-ready TVET governance frameworks in developing economies undergoing rapid socio technical transformation.